2010
DOI: 10.1590/s1516-35982010001200004
|View full text |Cite
|
Sign up to set email alerts
|

Perdas, características fermentativas e valor nutritivo da silagem de capim-elefante contendo subprodutos agrícolas

Abstract: RESUMO -O experimento foi conduzido para avaliar as perdas por gases e efluente, as características fermentativas e o valor nutritivo de silagens de capim-elefante contendo como aditivos farelo de mandioca, casca de café ou farelo de cacau.Utilizou-se delineamento inteiramente casualizado, em esquema fatorial 3 × 4, com três aditivos avaliados em quatro níveis (0, 10, 20 e 30% da matéria natural), cada um com cinco repetições. O material foi acondicionado em silos de PVC por 60 dias. Após abertura dos silos, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
3
18

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 14 publications
3
15
3
18
Order By: Relevance
“…These results can be related to the lower DM content of the silages of the present study. Andrade et al (2010) found that the inclusion of 14.2% of the cocoa meal was sufficient to inhibit effluent loss, different from the present study in that the addition of only 10% of mango residue allowed lower effluent losses (6,89 kg/ton NM). Negrão et al (2016) verify decrease of effluent and gas losses using rice meal in the silage of Brachiaria decumbens.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…These results can be related to the lower DM content of the silages of the present study. Andrade et al (2010) found that the inclusion of 14.2% of the cocoa meal was sufficient to inhibit effluent loss, different from the present study in that the addition of only 10% of mango residue allowed lower effluent losses (6,89 kg/ton NM). Negrão et al (2016) verify decrease of effluent and gas losses using rice meal in the silage of Brachiaria decumbens.…”
Section: Resultscontrasting
confidence: 99%
“…These lower values could be explained by the low content of DM (19.9%) and MM (2.40%) of the additive used, while the reduction of the NFC content accompanied the decrease in DM. The minimum DM content obtained in this study was close to that registered by Andrade et al (2010) of 29.7% DM, when evaluating elephant grass ensiling with 20% cocoa meal; and by Azevedo et al 2017, of 29.8% DM, using 16.1% mango residue in the elephant grass silage. However, it was superior to the elephant grass silages evaluated by Rêgo et al (2010) 27.9% DM, with the addition of 16% by-product of the mango processing; by Ferreira et al (2015) that obtained 27% DM with addition of 14% dehydrated cashew residue and by Ferrari Junior et al 2009which added 10% citrus pulp and reached 24.9% DM.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Samples from the silos were taken to determine the chemical composition (Silva and Queiroz, 2002), pH, and N-NH 3 (Campos et al, 2004). The loss of total dry matter (DM) and the loss due to gas production were calculated (Andrade et al, 2010). The effluent was determined by measuring the difference in the weight of the sand and silo prior and after ensiling in relation to the amount of green matter.…”
Section: Methodsmentioning
confidence: 99%
“…ANDRADE et al (2010), usando farelo de mandioca, farelo de cacau ou casca de café em silagens de capim Elefante, observaram que o farelo de cacau usado no nível de 14,23% foi o resíduo mais eficiente em reduzir a produção de efluentes. Entretanto, para o farelo de mandioca só foram observados resultados positivos quando o nível foi de 25,63%.…”
Section: Tabela 5 Equações De Regressão Para Interação Níveis/resíduunclassified